2009
DOI: 10.1634/theoncologist.2009-0078
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Breast Cancer: Therapeutic Options According to Molecular Subtypes and Prior Adjuvant Therapy

Abstract: In spite of advances in treatment strategies, about 25%-40% of patients with breast cancer still eventually develop metastatic disease that is largely incurable. Treatment goals vary from symptom control to lengthening survival, mainly on the basis of patient age and performance status, tumor biology, site and extent of disease, and prior therapies. In particular, breast cancer molecular characterization allows for the identification of breast cancer subtypes with distinct biological features, a distinct clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(69 citation statements)
references
References 106 publications
0
65
0
4
Order By: Relevance
“…In this study, we showed that E2 and EGF, major prometastatic growth factors in breast cancer (44)(45)(46), specifically repress let-7g expression and subsequently increase GAB2 and FN1 expression, which, in turn, cooperatively increased the activity of p44/42 MAPK and MMP-2/MMP-9. It has been reported recently that the p44/42 MAPK cascade may repress let-7 expression either via activating LIN28 transcription to affect primary let-7g processing (47) or via phosphorylating TAR RNA-binding protein, a critical component of miRNA-generating complex, to suppress the expression of let-7 miRNAs (36).…”
Section: Discussionmentioning
confidence: 74%
“…In this study, we showed that E2 and EGF, major prometastatic growth factors in breast cancer (44)(45)(46), specifically repress let-7g expression and subsequently increase GAB2 and FN1 expression, which, in turn, cooperatively increased the activity of p44/42 MAPK and MMP-2/MMP-9. It has been reported recently that the p44/42 MAPK cascade may repress let-7 expression either via activating LIN28 transcription to affect primary let-7g processing (47) or via phosphorylating TAR RNA-binding protein, a critical component of miRNA-generating complex, to suppress the expression of let-7 miRNAs (36).…”
Section: Discussionmentioning
confidence: 74%
“…P-53 mutation and cell proliferation rate in breast cancer are important markers for poor prognostic prediction. Luminal A subtype cancers also had lower recurency rate (27.8%) and higher survival rate (median survival rate: 2.2 years) in compare to non luminal cancers (Eroles et al, 2012;Guarneri et al, 2009). A study in Chinese cancer women found that luminal A subtype had the highest locoregional relaps -free survival (93.2%), distant metastasis-free survival (91.5%) and disease free survival rates (87.5%) at 5 years, while Her-2+ subtypes showed the highest rate reccurence (27.5%) and locoregional recurrence (11.4%) (Jia et al, 2014).…”
Section: P=0129mentioning
confidence: 94%
“…Patients with luminal-A breast cancer have a good prognosis; the relapse rate is significantly lower than the other subtypes. Recurrence is common in bone, whereas liver, lung and central nervous system metastases occur in less than 10% of patients and treatment is mainly based on hormonal therapy [15,16] .…”
Section: Luminal-amentioning
confidence: 99%